1. Представьте в виде многочлена:
а) ( у – 4)(у – 5) б) (х – 3)(х2 + 2х – 6)
в) (3а + 2b)(5а – b)

2. Разложите на множители:
а) b(b + 1) – 3(b + 1) б) са – сb + 2а - 2b

3. Упростите выражение:
(а2 – b2)(2а + b) - аb( а + b)

а ) 2а3 +в3 – 3ав2 б) 2а3 - в3 – 3ав2 в) 2а3 - в3 + 3ав2

4. Докажите тождество: ( х - 3)( х + 4) = х( х + 1) – 12.

1

Ответы и объяснения

2014-03-13T02:22:55+00:00
1.a)(y-4)(y-5)=y^2-9y+20
1.б)(x-3)(x2+2x-6)=x3+2x2-6x-3x2-6x+18=x3-x2-12x+18
1.в)(3a+2b)(5a-b)=15a2-3ab+10ab-2b2=15a2+7ab-2b2